Engineering polymeric and hybrid microparticles as novel controlled release systems - Luo, Daniel Chin Shiuan (2014)
Controlled drug release systems offer improved efficiency, reduced side-effects, and enhanced patient compliance over conventional drugs. While poly (lactic-co-glycolic) acid (PLGA) remains a popular candidate for controlled release of drugs and biomolecules, this single material formulation possesses low encapsulation efficiency and high initial burst release in release profile. In view of this, numerous efforts have been spent to design a variety of particle types encompassing different sizes, composites, and morphologies to improve drug delivery. However, none of the systems were able to produce particles with both improved loading efficiency and controlled release profile. In this study, incorporation of hydrogel core (alginate) in PLGA microparticles demonstrated higher loading efficiency and low release profile. Furthermore, combination of fabrication techniques enabled development of a wider range of controlled release formulations. Thereafter, in vitro experiments demonstrated a variety of loading capabilities for polymer-hydrogel composite microparticles in mesenchymal stem cells (MSCs). Hence, novel combinations of polymeric and hybrid particles served to overcome low encapsulation efficiency and provide tailored drug release profiles.